2020
DOI: 10.3892/mmr.2020.11029
|View full text |Cite
|
Sign up to set email alerts
|

7‑Difluoromethyl‑5,4'‑dimethoxygenistein exerts anti‑angiogenic effects on acute promyelocytic leukemia HL‑60 cells by inhibiting the TLR4/NF‑κB signaling pathway

Abstract: angiogenesis plays an important role in the development and metastasis of tumors, and anti-angiogenesis agents are used to treat tumors. For example, the acute promyelocytic leukemia (aPl) may be treated with arsenic trioxide. angiogenesis in aPl is a multi-step dynamic equilibrium process coordinated by various angiogenic stimulators and inhibitors, which play key roles in the occurrence, progression and chemosensitivity of this disease. our research group previously synthesized 7-difluoromethyl-5,4'-dimethox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Our previous studies reported that GEN and its derivative can protect against lysophosphatidylcholine-induced VEC injury, inhibit macrophage foaming, reduce VSMC proliferation and migration, and inhibit the angiogenesis of HL-60 cells via the Toll-like receptor 4 signaling pathway ( 29 31 ). The present study was designed to investigate the effects and molecular mechanisms of GEN on chronic vascular inflammatory response by stimulating C57BL/6 mice and human umbilical vein (HUV) ECs with LPS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies reported that GEN and its derivative can protect against lysophosphatidylcholine-induced VEC injury, inhibit macrophage foaming, reduce VSMC proliferation and migration, and inhibit the angiogenesis of HL-60 cells via the Toll-like receptor 4 signaling pathway ( 29 31 ). The present study was designed to investigate the effects and molecular mechanisms of GEN on chronic vascular inflammatory response by stimulating C57BL/6 mice and human umbilical vein (HUV) ECs with LPS.…”
Section: Introductionmentioning
confidence: 99%